Transcriptome-wide association study reveals cholesterol metabolism gene Lpl is a key regulator of cognitive dysfunction - Hu, Wei; Liu, Jian; Hu, Yaorui; Xu, Qingling; Deng, Tingzhi; Wei, Mengna; Lu, Lu; Mi, Jia; Bergquist, Jonas; Xu, Fuyi; Tian, Geng (Frontiers in Molecular Neuroscience, 2022)
Cholesterol metabolism in the brain plays a crucial role in normal physiological function and its aberrations are associated with cognitive dysfunction. The present study aimed to determine which cholesterol-related genes play the key role in cognitive dysfunction and to dissect its underlying molecular mechanisms using a systems genetics approach in the BXD mice family. We first systematically analyzed the association of hippocampal mRNA expression of 280 related to cholesterol metabolism with cognition related traits and identified Lpl is a key regulator. This was further confirmed by phenome wide association studies that indicates Lpl associates with hippocampus volume residuals and anxiety related traits. By performing expression quantitative trait locus mapping, we demonstrate that Lpl is strongly cis regulated in the BXD hippocampus. We also identified 3364 transcripts that are significantly (p < 0.05) correlated with the Lpl expression. Those genes mainly involve in the regulation of neuron related traits through MAPK signaling pathway, axon guidance, synaptic vesicle cycle, and NF-kappa B signaling pathway. Further, Protein-protein interaction network analysis identified several direct interactors of Lpl, including Rab3a, Akt1, Igf1, Crp, and Lrp1, which indicates that Lpl involves in the regulation of cognitive dysfunction through Rab3a mediated synaptic vesicle cycle and Akt1/Igf1/Crp/Lrp1 mediated MAPK signaling pathway. Our findings demonstrate the importance of the Lpl, among the cholesterol-related genes, in the regulation of cognitive dysfunction, and highlight the potential signaling pathways, which may serve as novel therapeutic targets for the treatment of cognitive dysfunction.